Effects of 3,4-diaminopyridine on myasthenia gravis: Preliminary results of an open-label study - Ceccanti, Marco; Libonati, Laura; Ruffolo, Gabriele; Cifelli, Pierangelo; Moret, Federica; Frasca, Vittorio; Palma, Eleonora; Inghilleri, Maurizio; Cambieri, Chiara (Frontiers in Pharmacology, 2022)
Background: 3,4-diaminopyridine (3,4-DAP) can lead to clinical and electrophysiological improvement in myasthenic syndrome; it may thus represent a valuable therapeutic option for patients intolerant to pyridostigmine. Objective: to assess 3,4-diaminopyridine (3,4-DAP) effects and tolerability in patients with anti-AChR myasthenia gravis. Method: Effects were monitored electrophysiologically by repetitive nerve stimulation (RNS) and by standardized clinical testing (QMG score) before and after a single dose administration of 3,4-DAP 10 mg per os in 15 patients. Patients were divided according to their MGFA class into mild and severe. Results: No significant side effects were found, apart from transient paresthesia. 3,4-DAP had a significant effect on the QMG score (P=0.0251), on repetitive nerve stimulation (P=0.0251), and on the forced vital capacity (P=0.03), thus indicating that it may reduce the level of disability and the decremental muscle response. When the patients were divided according to the MGFA classification, 3,4-DAP showed a positive effect in the severe group, either for the QMG score (P=0.031) or for the RNS decrement (P=0.031). No significant difference was observed in any of the outcome measures within the mild group (P>0.05). A direct effect of 3,4-DAP on nicotinic ACh receptors (nAChRs) was excluded since human nAChRs reconstituted in an expression system, which were not affected by 3,4-DAP application. Conclusion: Our results suggest that 3,4-DAP may be a useful add-on therapy, especially in most severe patients or when immunosuppressive treatment has not yet reached its full effect or when significant side-effects are associated with anticholinesterase.